L`importance de la quantification de la charge d`entraînement: exemple d`un modèle - Sedeaud, A.; Sène, J.M.; Krantz, N.; Saulière, G.; Moussa, I.; Toussaint, J.F. (Science & Sports, 2018)
Objectives: Emphasize the importance of setting up training load quantification models in sport. News: Sometimes neglected due to its time-consuming aspect, the quantification of training loads proves to be of great interest nevertheless, including in high performance sport. It is essential to place load quantification at the center of the training program so that it regains its main role within practice. Perspectives: This will have to go through the setting up of mixed models, including external and internal loads. Recent articles have placed internal loads as predominant indicators, which highlight the athlete's knowledge on how they perceive fatigue, recovery or session intensity. A recent model of loads ratio taking into account the chronic load and the acute load seems extremely relevant. This reflection on acute/chronic ratios needs to be extrapolated to other variables of follow-up and to cross with the monitoring of fatigue and injuries. Conclusion: This model is useful for physical preparation, training monitoring, injury prevention and reathletisation in accordance to competitive requirements. Moreover, the computing of the ratio load could be transferable to all sports and all levels.